Job Retention Among Resettled Refugees in The US:The Importance of Context. (13th December 2020) - Crea, Thomas M; Tobin, Emma; Young, Ann-Elizabeth; Ko, Christian; Weber, Alexandra
Abstract: The primary objective of the US refugee resettlement program is for beneficiaries to achieve economic self-sufficiency. Yet, little research has examined the extent to which this objective has been achieved, nor the programmatic and contextual variables that influence this outcome. This study examines how beneficiaries' individual and job characteristics are associated with the likelihood of job retention after 90 days of employment. Data were obtained on 1787 refugees served by the International Institute of New England from March 2015 to January 2019. Logistic regression models were used to examine the predictors of retention in four cities (Boston, MA; Lowell, MA; Manchester, NH; and Nashua, NH). Different patterns emerged across cities, related to factors such as pay, educational level, legal immigration status, job permanency, and gender. The concept of self-sufficiency is closely linked to the context of resettlement and thus requires more careful articulation as a goal of the refugee resettlement program.